Barnacle geese achieve significant energetic savings by changing posture. - Peter G Tickle; Robert L Nudds; Jonathan R Codd (PLoS ONE)
Here we report the resting metabolic rate in barnacle geese (Branta leucopsis) and provide evidence for the significant energetic effect of posture. Under laboratory conditions flow-through respirometry together with synchronous recording of behaviour enabled a calculation of how metabolic rate varies with posture. Our principal finding is that standing bipedally incurs a 25% increase in metabolic rate compared to birds sitting on the ground. In addition to the expected decrease in energy consumption of hindlimb postural muscles when sitting, we hypothesise that a change in breathing mechanics represents one potential mechanism for at least part of the observed difference in energetic cost. Due to the significant effect of posture, future studies of resting metabolic rates need to take into account and/or report differences in posture.